Flâneur widziany oczyma flâneura. Próba przeanalizowania obrazu obserwatora tłumu kreowanego przez Waltera Benjamina - Szurgot-Prus, Ewelina (Studia Europaea Gnesnensia, 2015)
This paper discusses the figure of flâneur , the urban observer. By way of the perspective adopted by Walter Benjamin, I attempt to identify all aspects of flâneurism. What is more, I try to ascertain the existence of correlations between the writer (Walter Benjamin) and the flâneur he described.